Effects of seedbed preparation methods on cowpea yield in Alfisols and Oxisols in semiarid West Africa - Muleba, N.; Brockman, F. (1991)
Tied-ridge techniques have not been used to improve seed yield in cowpeas, so experiments were conducted in Burkina Faso in the Sudan savannah zone on an Alfisol at five slope-positions on the toposequence, using two dates of planting for three consecutive years; and in the northern Guinea savannah zone, at a mid-slope position on an Oxisol with one date of planting for two consecutive years. In these trials, the effect of planting cowpeas on tied-ridge seedbeds was compared with planting on the flat. The plots were tractor-ploughed to 25 cm depth prior to the establishment of seedbed preparation methods. Tied-ridge seedbeds eliminated or reduced runoff, increased soil water storage and reduced severe seed yield losses during protracted dry spells in the Sudan savannah zone on an Alfisol, but they had no effect at all on cowpea yield in the northern Guinea savannah zone on an Oxisol. In the Alfisol, tractor ploughing and early planting were not adequate to reduce runoff and the cowpeas were subjected to severe yield loss during dry periods.